Substrate scope of a dehydrogenase from Sphingomonas species A1 and its potential application in the synthesis of rare sugars and sugar derivatives. Issue 4 (26th April 2018) - Beer, Barbara; Pick, André; Döring, Manuel; Lommes, Petra; Sieber, Volker
Summary: Rare sugars and sugar derivatives that can be obtained from abundant sugars are of great interest to biochemical and pharmaceutical research. Here, we describe the substrate scope of a short‐chain dehydrogenase/reductase from Sphingomonas species A1 (SpsADH) in the oxidation of aldonates and polyols. The resulting products are rare uronic acids and rare sugars respectively. We provide insight into the substrate recognition of SpsADH using kinetic analyses, which show that the configuration of the hydroxyl groups adjacent to the oxidized carbon is crucial for substrate recognition. Furthermore, the specificity is demonstrated by the oxidation ofd ‐sorbitol leading tol ‐gulose as sole product instead of a mixture ofd ‐glucose andl ‐gulose. Finally, we applied the enzyme to the synthesis ofl ‐gulose fromd ‐sorbitol in an in vitro system using a NADH oxidase for cofactor recycling. This study shows the usefulness of exploring the substrate scope of enzymes to find new enzymatic reaction pathways from renewable resources to value‐added compounds. Abstract : An oxidoreductase from Sphingomonas species A1 was investigated toward its substrate scope with aldonates and polyols. Conclusions on substrate recognition were drawn upon kinetic parameters and HPLC analyses of the reaction products. Furthermore, the enzyme was applied to synthesize the rare sugarl ‐gulose fromd ‐sorbitol with cofactor recycling using an NADH oxidase.